Profanacja czy innowacja? Dekonstrukcja stroju ludowego w konwencji folk fashion - Toboła-Feliks, Magdalena (Studia Etnologiczne i Antropologiczne, 2019)
In the fashion world of today there appears an increasing number of projects whose overall theme are traditional folk costumes. On the one hand, designers embark upon representing folk costumes faithfully, yet on the other, only some reverberations are present in the “folk fashion” current, whose framework encompasses aleatoric associations of native patterns that compose a peculiar type of axiological mosaic. The foregoing constitutes a stimulus for cultural-imbued creativity, while concurrently being an alternative for mass production. In many cases, attempts to resuscitate tradition translate into space for re-interpreting it, the ramification of which is, in turn, a challenging research area for contemporary ethnology and cultural anthropology.